The datafication of e-sports players and specialty hotels as venues for online communities - Lei, Angel (Global Journal of Social Sciences Studies, 2025)
This study investigates E-sports hotels as hybrid environments where digital networks and physical infrastructures converge to transform leisure into data-driven labor. The purpose is to analyze how these venues shape gamer identity, social belonging, and economic participation through algorithmic governance and datafication. Using an interpretive framework grounded in media studies, sociology, and computational modeling, the paper conceptualizes E-sports hotels as nodes within a tripartite network linking players, platforms, and physical spaces. The methodology integrates theoretical synthesis with a formalized utility model that represents player decision-making based on convenience, belonging, environmental quality, and algorithmic influence. Findings reveal that players’ perceived choices are strongly conditioned by data-driven recommendation systems and that a sense of belonging exerts greater influence on consumer behavior than traditional factors such as price or location. E-sports hotels convert this social validation into economic and algorithmic value, reinforcing a feedback loop between identity formation and platform visibility. The study concludes that these venues operate not merely as hospitality businesses but as infrastructures of platform capitalism, where user behavior continuously generates data capital. The practical implications suggest that understanding such hybrid spaces is essential for policymakers, designers, and cultural theorists seeking to navigate the intersections of leisure, data governance, and emerging digital economies.